Global Radiative Impacts of Black Carbon Acting as Ice Nucleating Particles. Issue 20 (12th October 2020) - McGraw, Zachary; Storelvmo, Trude; Samset, Bjørn Hallvard; Stjern, Camilla Weum
Abstract: Black carbon (BC) aerosols from incomplete combustion generally warm the climate, but the magnitudes of their various interactions with climate are still uncertain. A key knowledge gap is their role as ice nucleating particles (INPs), enabling ice formation in clouds. Here we assess the global radiative impacts of BC acting as INPs, using simulations with the Community Earth System Model 2 climate model updated to include new laboratory‐based ice nucleation parameterizations. Overall, we find a moderate cooling through changes to stratiform cirrus clouds, counteracting the well‐known net warming from BC's direct scattering and absorption of radiation. Our best estimates indicate that BC INPs generally thin cirrus by indirectly inhibiting the freezing of solution aerosol, with a global net radiative impact of −0.13 ± 0.07 W/m 2 . Sensitivity tests of BC amounts and ice nucleating efficiencies, and uncertainties in the environment where ice crystals form, show a potential range of impacts from −0.30 to +0.02 W/m 2 . Plain Language Summary: Airborne black carbon particles generally warm Earth's surface and lower atmosphere, but the individual mechanisms that contribute to and offset this effect are difficult to measure and poorly understand. Highly uncertain is the impact of black carbon's ability to enable ice to form in clouds. Here we use simulations of Earth's climate to estimate the global impact of black carbon's role in ice formation. We find that, in this role, black carbon causes a moderate cooling. This is mostly due to black carbon forming ice in high, thin clouds. Using a mix of simulations to represent the range of plausible circumstances, we calculate bounds on this impact. Key Points: Anthropogenic black carbon (BC) thins cirrus clouds by inhibiting homogeneous nucleation, inducing moderate global cooling The cooling impact saturates at high BC number and nucleating efficiency, due to cirrus thickening via enhanced heterogeneous ice formation BC cooling by cirrus thinning requires colocation of the aerosol with abundant, medium‐thickness homogeneously formed cirrus